An Assessment of How Urban Crime and Victimization Affects Life Satisfaction - Carlos Medina
We assess the effect of the homicide rate, individual´s perception of security in their neighborhood of residence, and of the effect of their having been victimized, on life satisfaction. We find a negative effect of the homicide rate on life satisfaction for the subsample of individuals living in their current houses for at least 10 years or more, who had moved to that place at some point in the past. We also find a positive and robust effect of the perception of security in the households´neighborhood for the whole sample, and for different subsamples considered. Having been victim of an offense is also robustly negatively related to life satisfaction, in particular in the cases where the offense was robbery.Quality of Life, Life Satisfaction, Crime. Classification JEL: I32, K40, K42.